Step-by-step explanation
The vertex form of a quadratic function is:
![\begin{gathered} y=a(x-h)^2+k \\ \text{ Where} \\ (h,k)\text{ is the vertex of the parabola } \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tbamwilvkbvsyb4wknophsirrf36vi2kc8.png)
The standard form of a quadratic function is:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
We can do the following steps to solve the exercise.
Step 1: We replace the values of h,k, x, and y into the vertex form of a quadratic equation, and we solve for a.
![\begin{gathered} h=1 \\ k=-5 \\ x=3 \\ y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ial9wgvvev2pvj6pnq6195bzxrymgt0hgf.png)
![\begin{gathered} y=a(x-h)^(2)+k \\ -1=a(3-1)^2-5 \\ -1=a(2)^2-5 \\ -1=4a-5 \\ \text{ Add 5 from both sides} \\ -1+5=4a-5+5 \\ 4=4a \\ \text{ Divide by 4 from both sides} \\ (4)/(4)=(4a)/(4) \\ 1=a \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/k33okla5pw1abmfo26gjigjldesvd21xli.png)
Step 2: We replace the values of a,h, and k into the vertex form of a quadratic equation.
![\begin{gathered} y=a(x-h)^(2)+k \\ y=1(x-1)^2-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/z2j64mikfm3zjcdxmuy3f3c8r7yzk2rh8e.png)
Step 3: We expand the expression inside the parentheses and combine like terms to convert the function into its standard form.
![\begin{gathered} y=1(x-1)^(2)-5 \\ y=(x-1)^2-5 \\ y=(x-1)(x-1)-5 \\ \text{ Apply the distributive property} \\ y=x(x-1)-1(x-1)-5 \\ y=x*x-x*1-1*x-1*-1-5 \\ y=x^2-x-x+1-5 \\ y=x^2-2x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/vdsh3fe8osxpom8fmvursrds1b3vn5h9u3.png)
Answer
The equation of the graph in standard form is:
![y=x^(2)-2x-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/eazwzv8k3k2uvbny4oipcs5k3h0wzox42y.png)